The Impact of Science-Fiction Movies on the Self-Efficacy Perceptions of Their Science Literacy of Science Teacher Candidates - ÖNEN ÖZTÜRK, FATMA (EDAM, 2017)
This study aims to determine the impact of science-fiction movies on science teacher candidates' selfefficacy perceptions of their scientific literacy. A mixed methodology was used in the study, which was conducted in the classes of Natural Sciences and Society with a total of 20 second-year teacher candidates from the department of primary education science teaching at a public university in Istanbul during the spring semester of the 2012-2013 academic year, over five weeks; 10 science-fiction movies were watched by these students in this period. Data were collected using a survey designed to capture self-efficacy perception of scientific and technological literacy that was composed of a 33-item instrument, with a 5-point Likert scale for responses to each item, and seven interview questions. The research data were assessed using the t-test for dependent samples, the descriptive statistics technique found in SPSS, and the descriptive analysis method, a qualitative method. The results show that science-fiction movies had a positive impact on the teacher candidates' self-efficacy perceptions of their scientific literacy. Furthermore, teacher candidates rated themselves moderately capable in 17 items in response to the survey instrument in the pre-implementation period, but this figure decreased to five following the implementation period.
Keywords: Science fiction movie; Science teacher candidate; Scientific literacy; Self-efficacy perception; Self-efficacy perception of scientific literacy; INSTRUCTION; BELIEFS; FILMS